The study of the AlN/Si(111) epitaxial structures grown by PA MBE via coalescence overgrowth of AlN nanocolumns. (December 2020) - Shubina, K Yu; Mokhov, D V; Berezovskaya, T N; Nikitina, E V; Mizerov, A M; Bouravleuv, A D
Abstract: The AlN/Si(111) epitaxial structures were synthesized by coalescence overgrowth of AlN nanocolumns using PA MBE technique. Such epitaxial structures can be used as a buffer layer for obtaining high quality AlN and GaN layers. Structural, electrical and chemical properties of these samples were studied. For the first time it was demonstrated that the etching of the obtained type of AlN/Si(111) structures in KOH can become a promising method for obtaining high quality free-standing AlN and GaN.